A lidar method for determining internal wave characteristics - Dolin, L. S.; Dolina, I. S.; Savel’ev, V. A. (Izvestiya. Atmospheric and oceanic physics, 2012)
An analytical model of lidar imaging of pycnoclinic internal waves (IWs) is developed. The IW image is shown to represent a superposition of two images: reflective and shadow. The former reflects perturbations in the profile of the light backscattering coefficient in the IW field, and the latter reflects perturbations in the optical thickness of the water layer, in which the IW disturbed the horizontal uniformity of optical characteristics. Algorithms for reconstructing the IW field from these images are proposed. It is shown that the shadow image, unlike the reflective one, is insensitive to fine details of the profiles of hydrooptical characteristics and can be used for determining IW parameters on the basis of very rough data on optical properties of water. The possibility of determining the mode composition as well as the lengths and amplitudes of IW modes is demonstrated by using the Barents Sea as an example and invoking actual and simultaneously measured profiles of the water density and light attenuation coefficient.